Predictors for unfavorable prognosis after stroke with perforator artery disease - Song, Linghua; Lou, Xiaoli; Han, Wenhao; Yang, Lihui; Guo, Siping; Jiang, Yasi; Peng, Hao; Hao, Yonggang (Frontiers in Neurology, 2024)
Background and purpose Perforator artery disease (PAD) is an important subtype of ischemic stroke. The risk factors affecting the prognosis of patients with PAD are unclear. This study aimed to investigate the risk factors affecting the unfavorable prognosis of PAD. Methods Patients with PAD were enrolled from Dushu Lake Hospital Affiliated to Soochow University and diagnosed as stroke with PAD during the period from September 2021 to July 2023 and followed up with a modified Rankin Scale (mRS) after 90 days, defining the mRS of 0–2 as a group with favorable prognosis, and 3–6 as a group with unfavorable functional outcome. Logistic regression was used to identify predictors for PAD. Multiple logistic regression analysis and receiver operating characteristics (ROC) were used to identify predictors of unfavorable prognosis. Results Of the 181 enrolled patients, 48 (26.5%) were identified with unfavorable prognosis. On multivariate analysis, increased age (OR = 1.076, 95% CI: 1.012 ~ 1.144, p = 0.019), higher National Institutes of Health Stroke Scale (NIHSS) score at admission (OR = 2.930, 95% CI: 1. 905 ~ 4.508, p < 0.001), and increased neutrophil-to-lymphocyte ratio (NLR) (OR = 3.028, 95% CI: 1.615 ~ 5.675, p = 0.001) were independent risk factors for unfavorable prognosis in patients with PAD, and the area under the receiver operating characteristic curve was 0.590, 0.905, and 0.798, and the multi-factor diagnostic model (Model 2) showed reliable diagnostic specificity and sensitivity (area under the curve = 0.956, p < 0.001, specificity 0.805, sensitivity 0.958, accuracy 0.845). Conclusion Increased baseline NLR and NIHSS score and aging may be independent risk factors for unfavorable prognosis of patients with PAD. NLR can be used as a potential biological indicator to predict the prognosis of stroke with PAD.